Impact Culture: Transforming How Universities Tackle Twenty First Century Challenges - Reed, Mark S.; Fazey, Ioan (Frontiers in Sustainability, 2021)
New ways of doing research are needed to tackle the deep interconnected nature of 21st Century challenges, like climate change, obesity and entrenched social and economic inequalities. While the impact agenda has been shaping research culture, this has largely been driven by economic imperatives, leading to a range of negative unintended consequences. Alternative approaches are needed to engage researchers in the pursuit of global challenges, but little is known about the role of impact in research cultures, how more or less healthy “impact cultures” might be characterised, or the factors that shape these cultures. We therefore develop a definition, conceptual framework and typology to explain how different types of impact culture develop and how these cultures may be transformed to empower researchers to co-produce research and action that can tackle societal challenges with relevant stakeholders and publics. A new way of thinking about impact culture is needed to support more societally relevant research. We propose that healthy impact cultures are based on: i) rigorous, ethical and action-oriented research; ii) underpinned by the individual and shared purpose, identities and values of researchers who create meaning together as they generate impact from their work; iii) enabling multiple impact sub-cultures to develop among complementary communities of researchers and stakeholders, which are porous and dynamic, enabling these communities to work together where their needs and interests intersect, as they build trust and connection and attend to the role of social norms and power; and iv) enabled with sufficient capacity, including skills, resources, leadership, strategic and learning capacity. Based on this framework we identify four types of culture: corporate impact culture; research “and impact” culture; individualistic impact culture; and co-productive impact culture. We conclude by arguing for a bottom-up transformation of research culture, moving away from the top-down strategies and plans of corporate impact cultures, towards change driven by researchers and stakeholders themselves in more co-productive and participatory impact cultures that can address 21st Century challenges.